EFFECTIVE BRANDING USING SOCIAL MEDIA AND DIGITAL MARKETING: STUDY IN IRAQ - Author Dr.Maher Fadhil MOHAMMED; Mohammed Sami Rashid ALKHATEEB; ODAY JADDOA ABED ALFALAHI (Scholar Express Journals, 2024)
In the unexpectedly evolving virtual platforms of Iraq, information how clients interact with brands on social media and digital marketing systems is important for effective branding. This examine explores customer behaviors and choices closer to social media usage, brand engagement, and perceptions of virtual marketing, supplying insights into the factors that pressure a success digital branding techniques within the vicinity
Keywords: Digital branding; social media; consumer conduct